ROLA NAUCZYCIELA – MITY I SLOGANY A RZECZYWISTOŚĆ - Komorowska, Hanna (Neofilolog, 2019)
The article presents an overview of the situation in language teaching and teacher education in Poland. An attempt has been made to evaluate the developments of the last 25 years in the Polish educational landscape in the field of language teaching, protection and promotion of minority and regional languages, pre- and in-service teacher education. Special attention has been given to expectations vis-à-vis the teaching profession in Poland and abroad, challenges arising in teacher training institutions, difficulties teachers encounter in their everyday functioning as well as their training needs. Controversial issues arising from inconclusive research results have also been identified. In the final part of the text ideas are provided for quantitative and qualitative research and its role in pre- and in-service teacher education.